Penyuluhan Digital Marketing di Yayasan Pondok Pesantren Modern Yatim dan Dhuafa Madania Yogyakarta - Khairi, Ardhi; Sari, Niken Permata; Sari, Utami Tunjung; Bahri, Bahri; Artha, Bhenu; Asri, Cahya Purnama; Hadi, Antonius Satria (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This community service activity provides counseling to students and administrators of YPPMD Madania which aims to provide additional understanding and knowledge about digital marketing, so that later the students and administrators of YPPMD Madania can use digital marketing in their business. This community service activity was carried out using lecture and question and answer methods. The benefits that can be obtained by participants from this community service activity include increased knowledge, understanding, and experience of YPPMD Madania students and administrators about digital marketing.